S-Benzyl 3-[1-(6-methylpyridin-2-yl)ethylidene]dithiocarbazate: crystal structure and Hirshfeld surface analysis - Siti Aminah Omar,; Chah, Chee Keong; Ravoof, Thahira Begum S. A.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (2018)
In the title dithiocarbazate ester, C16H17N3S2 (systematic name: (Z)-{[(benzylsulfanyl)methanethioyl]amino}[1-(6-methylpyridin-2-yl)ethylidene]amine), the central methylidenehydrazinecarbodithioate (C2N2S2) core is almost planar (r.m.s. deviation = 0.0111 A ° ) and forms dihedral angles of 71.67 (3)⁰ with the approximately orthogonally inclined thioester phenyl ring, and 7.16 (7)⁰ with the approximately coplanar substituted pyridyl ring. The latter arrangement and the Z configuration about the imine-C N bond allows for the formation of an intramolecular hydrazine-N—H...N(pyridyl) hydrogen bond that closes an S(6)loop. In the crystal, phenyl-C—H....S(thione), methylene-C—H....(pyridyl), methylene- and phenyl-C—H....π(phenyl) contacts connect molecules into supramolecular layers propagating in the bc plane; the layers stack along the a axis with no directional interactions between them. The analysis of the Hirshfeld surface indicates the relative importance of an intralayer phenyl-H...H(pyridyl)contact upon the molecular packing.